From the Jungle to Social Media: Exploring the Phenomenon of "Celebrity" Elephants in Tesso Nilo National Park - Basyarul Aziz; Azlin Resiana; Khoirun Nisa Aulia Sukmani (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The conflict between humans and elephants in Indonesia continues to escalate due to land expansion and forest encroachment, forcing elephants to enter settlements and agricultural areas. This phenomenon has gained widespread attention, particularly through news coverage and social media. This study examines how social media, particularly Instagram, shapes public perceptions of elephants, specifically in Tesso Nilo National Park. Using a qualitative method with a phenomenological approach and virtual ethnography, this research explores the representation of elephants as "celebrities" shaped by Mahouts (elephant handlers) through their social media posts. The findings reveal that Instagram plays a role in creating two types of perceptions: physical reality and imagery. Physical reality perceives elephants as animals that need to be cared for, fed, monitored, and trained, while the imagery constructed through social media portrays elephants as individuals with unique personalities, attracting public attention and sympathy. Some elephants, such as Domang, Tari, and Harmoni, have gained "celebrity" status due to their interactions with Mahouts, which are shared on social media, fostering emotional connections between Instagram followers and these elephants. However, this phenomenon also raises ethical discussions regarding the treatment of elephants, such as the use of chains and Mahout communication tools. This study highlights that social media can be an effective tool for conservation by raising public awareness but also opens up debates and criticisms regarding the ethics of wildlife treatment.